2015
DOI: 10.1002/jms.3589
|View full text |Cite
|
Sign up to set email alerts
|

Epitope mapping of 7S cashew antigen in complex with antibody by solution‐phase H/D exchange monitored by FT‐ICR mass spectrometry

Abstract: The potential epitope of a recombinant food allergen protein, cashew Ana o 1, reactive to monoclonal antibody, mAb 2G4, has been mapped by solution-phase amide backbone H/D exchange (HDX) monitored by Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS). Purified mAb 2G4 was incubated with recombinant Ana o 1 (rAna o 1) to form antigen:monoclonal antibody (Ag:mAb) complexes. Complexed and uncomplexed (free) rAna o 1 were then subjected to HDX-MS analysis. Five regions protected from H/D exch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 51 publications
(79 reference statements)
0
18
0
Order By: Relevance
“…Using the same procedure to obtain a recombinant Ana o 1, Guan et al [66] demonstrated that two of the linear epitope-contributing peptide segments, which were previously reported by Wang et al [65], participate in a conformational epitope. Additionally, the authors also revealed three new peptide segments that are believed to function as independent linear epitopes when complexed with some antibodies and/or together, contributing to one or more conformational epitopes [66].…”
Section: Ana O 1-vicilinmentioning
confidence: 86%
“…Using the same procedure to obtain a recombinant Ana o 1, Guan et al [66] demonstrated that two of the linear epitope-contributing peptide segments, which were previously reported by Wang et al [65], participate in a conformational epitope. Additionally, the authors also revealed three new peptide segments that are believed to function as independent linear epitopes when complexed with some antibodies and/or together, contributing to one or more conformational epitopes [66].…”
Section: Ana O 1-vicilinmentioning
confidence: 86%
“…Linear epitopes, composed of a continuous amino acid sequence, have been detected by screening patient sera on sequential overlapping peptide libraries or allergen fragments. Conformational epitopes, composed of sterically closed amino acids upon folding, were characterized by phage display technique or mass spectrometry partly in combination with B‐cell epitope prediction web tools or software, although the use of these techniques still has to be proven in future studies …”
Section: Introductionmentioning
confidence: 99%
“…tools or software, although the use of these techniques still has to be proven in future studies. 6,[17][18][19][20][21] So far, it is impossible to discriminate between clinically relevant and irrelevant epitopes or combinations using current approaches and to use these differences as diagnostic or prognostic markers.…”
mentioning
confidence: 99%
“…Owing to its sequencing capability, MS is one “read-out” for many functional epitope-mapping approaches [2, 3]. Moreover, MS-based footprinting (e.g., HDX-MS) have successfully bridged high and low-resolution structural epitope mapping methods by reliably localizing the binding site at the peptide level [48]. …”
Section: Introductionmentioning
confidence: 99%